Local Wisdom Values in the Manjagit Parompa Sadun Tradition at Binanga Market, Barumun Tengah District - Anna Wahyuni Siregar; Syarbaini Saleh (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
This study aims to analyze the local wisdom values contained in the Manjagit Parompa Sadun tradition at Binanga Market, Barumun Tengah District, examine its relevance as a source of contextual learning in Social Studies education, and describe the social and cultural meanings of the tradition as understood by the community, especially the younger generation. The research uses a qualitative approach with ethnographic research methods. There are five research informants, consisting of customary leaders, religious leaders, Parompa Sadun practitioners or artisans, parents who have participated in the Manjagit Parompa Sadun tradition, and community figures. Data was collected through observation, in-depth interviews, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and drawing and verifying conclusions.  The validity of the data was tested through source triangulation, technique triangulation, and member checking. The research results show that the Manjagit Parompa Sadun tradition contains local wisdom values such as mutual cooperation, family ties based on the Dalihan Na Tolu system, religiosity, respect for elders, responsibility in raising children, and the preservation of local culture. This tradition is also highly relevant as a source of contextual learning in social studies because it includes concepts of social interaction, values and norms, cooperation, culture, and community life that can be connected to students' real-life experiences.  Besides that, people still see this tradition as a symbol of cultural identity, social solidarity, and a way to pass on cultural values to the younger generation, even though young people's understanding of its philosophical meaning still needs to be strengthened through the roles of families, traditional leaders, religious figures, communities, and educational institutions. This study emphasizes that the Manjagit Parompa Sadun tradition is not just a cultural heritage, but also a way to preserve local wisdom, strengthen character, and serve as a source of contextual learning that is relevant to modern educational needs.